Advances in the metrological traceability and performance of X-ray computed tomography. Issue 2 (2022) - Dewulf, Wim; Bosse, Harald; Carmignato, Simone; Leach, Richard
Abstract : X-ray computed tomography (XCT) is increasingly being used for evaluating quality and conformance of complex products, including assemblies and additively manufactured parts. The metrological performance and traceability of XCT nevertheless remains an important research area that is reviewed in this paper. The error sources influencing XCT measurement results are discussed, along with related qualification, calibration and optimization procedures. Moreover, progress on performance verification testing and on the determination of task-specific measurement uncertainty is covered. Results of interlaboratory comparisons are summarized and performance in various dimensional measurement fields is illustrated. Conclusions and an outlook for future research activities are also provided.